2020
DOI: 10.1177/1945892420972326
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Omalizumab Treatment in Patients With Recalcitrant Nasal Polyposis and Mild Asthma: A Multicenter Retrospective Study

Abstract: Background Chronic rhinosinusitis with nasal polyps (CRSwNP) is a clinical entity with specific features that impacts significantly on patient quality of life (QoL). CRSwNP is often associated with asthma and is difficult to control and manage despite pharmacological and/or surgical treatment. Omalizumab, a monoclonal anti-IgE antibody, has emerged as a putative therapeutic option. Objective To evaluate the effects of omalizumab on nasal polyp (NP) size and QoL assessed by Sino-Nasal Outcome Test-22 (SNOT-22) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…In a multicenter retrospective study, 23 patients with recalcitrant nasal polyposis and mild asthma were detected and in all patients, a significant and sustained reduction in total nasal endoscopic polyp score and lower SNOT-22 scores were observed over time. 19 In our study, we evaluated our patients monthly but here we did not determine statistics for each month.…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter retrospective study, 23 patients with recalcitrant nasal polyposis and mild asthma were detected and in all patients, a significant and sustained reduction in total nasal endoscopic polyp score and lower SNOT-22 scores were observed over time. 19 In our study, we evaluated our patients monthly but here we did not determine statistics for each month.…”
Section: Discussionmentioning
confidence: 99%
“…Mean SNOT-22 scores decreased from 58.96 at baseline to 19.71 at 12 months. 87 Similarly to dupilumab, discontinuation of omalizumab treatment in an extension study of patients from POLYP-1 and -2 resulted in worsening SNOT-22 scores and decreased nasal polyp score (NPS) and nasal congestion scores, although they remained improved above pretreatment levels. 85 Mepolizumab (GSK, Brentford, UK), a humanized mAb targeting IL-5, was submitted to the US Food and Drug Administration for approval in late 2020.…”
Section: Impact Of Treatment On Qol In Crswnpmentioning
confidence: 99%
“…It is intuitive to believe that patients with elevated serum IgE are more likely to have a significant change in objective treatment outcomes due to the mechanism of action of omalizumab. Currently, there is one omalizumab study that demonstrated no significant impact of baseline serum IgE levels on the nasal polyp size and SNOT-22 score [ 51 ]. However, this study was limited by its small population (n = 23) which caused their regression analysis to not follow the one in ten rule [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is one omalizumab study that demonstrated no significant impact of baseline serum IgE levels on the nasal polyp size and SNOT-22 score [ 51 ]. However, this study was limited by its small population (n = 23) which caused their regression analysis to not follow the one in ten rule [ 51 ]. Additional research is needed to confirm the impact of baseline IgE serology on omalizumab efficacy.…”
Section: Discussionmentioning
confidence: 99%